Glutathione levels are associated with methotrexate resistance in acute lymphoblastic leukemia cell lines - Canevarolo, Rafael Renatino; Melo, Carolina Pereira de Souza; Cury, Nathalia Moreno; Artico, Leonardo Luiz; Corrêa, Juliana Ronchi; Lau, Yanca Tonhasca; Mariano, Samara Sousa; Sudalagunta, Praneeth Reddy; Brandalise, Silvia Regina; Zeri, Ana Carolina de Mattos; Yunes, José Andrés (Frontiers in Oncology, 2022)
Methotrexate (MTX), a folic acid antagonist and nucleotide synthesis inhibitor, is a cornerstone drug used against acute lymphoblastic leukemia (ALL), but its mechanism of action and resistance continues to be unraveled even after decades of clinical use. To further understand the mechanisms of this drug, we accessed the intracellular metabolic content of 13 ALL cell lines treated with MTX. MTX altered the concentration of 31 out of 70 metabolites analyzed, suggesting inhibition of the glycine cleavage system, the pentose phosphate pathway, purine and pyrimidine synthesis, phospholipid metabolism, and bile acid uptake. We found that glutathione (GSH) levels were associated with MTX resistance in both treated and untreated cells, suggesting a new constitutive metabolic-based mechanism of resistance to the drug. Gene expression analyses showed that eight genes involved in GSH metabolism were correlated to GSH concentrations, 2 of which (gamma-glutamyltransferase 1 [GGT1] and thioredoxin reductase 3 [TXNRD3]) were also correlated to MTX resistance. Gene set enrichment analysis (GSEA) confirmed the association between GSH metabolism and MTX resistance. Pharmacological inhibition or stimulation of the main antioxidant systems of the cell, GSH and thioredoxin, confirmed their importance in MTX resistance. Arsenic trioxide (ATO), a thioredoxin inhibitor used against acute promyelocytic leukemia, potentiated MTX cytotoxicity in vitro in some of the ALL cell lines tested. Likewise, the ATO+MTX combination decreased tumor burden and extended the survival of NOD scid gamma (NSG) mice transplanted with patient-derived ALL xenograft, but only in one of four ALLs tested. Altogether, our results show that the cellular antioxidant defense systems contribute to leukemia resistance to MTX, and targeting these pathways, especially the thioredoxin antioxidant system, may be a promising strategy for resensitizing ALL to MTX.